Effect of Guidance Mode on Dynamic Performance of High Speed Cylindrical Roller Bearing Cage - Kaiwen Tian; Ming Qiu; Yibo Tang; Xiaoxu Pang (Jixie chuandong)
Aiming at the divergences in the selection of the guidance mode of the high-speed cylindrical roller bearing cage，a simulation model of the high-speed cylindrical roller bearing is established based on Adore. The effects of the number of rollers，radial clearance，cage guidance clearance and pocket hole clearance on cage slip rate and running stability are analyzed under the outer guidance mode and inner guidance mode，and the reliability of the simulation model is verified by the high-speed bearing slip test. The results show that when the inner ring rotates，the inner guidance mode is more beneficial than the outer guidance in preventing the cage from slipping. In the inner guidance mode，the smaller radial bearing clearance and guiding clearance can reduce the cage slip rate and improve the running stability. The pocket hole clearance has almost no effect on cage slip，but as the pocket hole clearance increases，the running stability of the cage becomes worse.